Interest Of Student SMPN 1 Painan Following Individual Counseling - Nofiani, Dea; Hariko, Rezki (Current Issues in Counseling, 2023)
Interest in participating in individual counseling services greatly influences the effectiveness of counseling. However, individual counseling services are still rarely used by students. As a result students become less interested in utilizing individual counseling services. This article aims to describe the interest of SMPN 1 Painan students in participating in individual counseling services. This article is a correlational quantitative research. The subjects in this article were students of SMPN 1 Painan with a total sample of 208 students selected by proportional random sampling technique. The instrument used in this article is the interest scale of students participating in individual counseling. The results of the study found that the interest of SMPN 1 Painan students to attend individual counseling was in the high category. It can be concluded that students of SMPN 1 Painan are highly interested in participating in individual counseling.